PELAYANAN HOLISTIK DALAM YESAYA 61:1-3 DAN IMPLIKASINYA BAGI PELAYANAN DI MASA PANDEMI COVID-19 - kristiawan, ragil (Shift Key : Jurnal Teologi dan Pelayanan, 2021)
The purpose of this study includes two parts. First to give an exposition to the holistic ministry of the Messiah in Isaiah 61: 1-3. Second, provide an explanation of the implications of this holistic service for services during the Covid-19 pandemic. The method used is qualitative with inductive characteristics of literature study. Isaiah 61: 1-3 describes the holistic ministry of the Messiah by preaching good news, preaching deliverance, announcing the year of God's grace, comforting, and giving joy to the people. The implications for services during the pandemic are evangelism services, social services, spiritual services, and Diakonia services. All forms of services are adapted to pandemic conditions by utilizing technology that is currently developing.Â